Analytical Method Development and Validation of RP-HPLC Method for Estimation of Linagliptin in Bulk and Pharmaceutical Dosage Form - B. Khaladkar, Vaibhav; U. Barge, Vijaya (Journal of Neonatal Surgery, 2025)
A simple, precise, and specific spectroscopy method for quantitative determination of Linagliptin in API and in pharmaceutical dosage form was developed and validated. The development was performed on a Zorbax SB Phenyl column (150 x 4.6 mm, 5 µm). The pH was adjusted to 3.2 with buffer solution: acetonitrile (75:25% v/v) at a 1.0 mL/min flow rate. Samples werelyzed using a UV-visible 2487 detector at 295 nm. The developed method complied with the system suitability study with an acceptable asymmetric factor and number of theoretical plates. The linearity was observed between 10–30 μg/mL concentrations (r² = 0.999). Method accuracy was observed as 99.7 %. The drug content was found within the acceptable limit in the intermediate precision study. The retention time was obtained at 2.73 min. This method was validated and applied to the determination of Linagliptin in pharmaceutical dosage form. (1)